Five-year outcomes of double kissing mini-culotte stenting vs. mini-culotte stenting using drug-eluting stents for the treatment of true coronary bifurcation lesions - Tu, Sheng; Zhang, Linlin; Tian, Qingqing; Hu, Fudong; Wang, Ying; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to compare the clinical outcomes of double kissing mini-culotte (DKMC) stenting with those of mini-culotte (MC) stenting in treating patients with true coronary bifurcation lesions (CBLs) in the clinical real world. Methods This retrospective observational cohort study included 180 consecutive patients with true CBLs (Medina type 1,1,1; 1,0,1; 0,1,1). All eligible patients underwent coronary angiography and percutaneous coronary intervention with two-stent techniques in our hospital; among them, 97 received DKMC treatment and 83 MC treatment. The primary clinical endpoints were the major adverse cardiovascular events (MACE), which included cardiac death, myocardial infarction, and target vessel/lesion revascularization (TVR/TLR). The secondary endpoints were stent thrombosis, in-stent restenosis, and individual components of MACE. Results Quantitative coronary angiography analysis (at 5 years) revealed that late lumen loss (0.25 ± 0.41 mm vs. 0.14 ± 0.32 mm, P = 0.032) and segmental diameter restenosis of the side branch (27.84 ± 12.34% vs. 19.23 ± 9.76%, P = 0.016) were lower in the DKMC treatment group than that in the MC treatment group. Notably, compared to that in the MC treatment group, the cumulative event rate of MACE at 5 years (22.8% vs. 8.3%, P = 0.007) and TVR/TLR (17.7% vs. 6.3%, P = 0.018) was higher in the DKMC treatment group, driven mainly by TVR/TLR. Especially, the DKMC group was related to a significant reduction in the primary and secondary endpoints in high-risk patients. Conclusion DKMC treatment was associated with less late lumen loss and restenosis in the side branch and a lower rate of cumulative MACE and TVR/TLR. DKMC treatment is more effective for treating true CBLs than MC treatment; however, these findings warrant further confirmation through a randomized clinical trial.